L-Proline nitrate: a recyclable and green catalyst for the synthesis of highly functionalized piperidines1. Issue 58 (25th June 2015) - Agrawal, Nikita R.; Bahekar, Sandeep P.; Sarode, Prashant B.; Zade, Sanjio S.; Chandak, Hemant S.
<x xml:space="preserve">Abstract</x> Multi-component synthesis of highly functionalized piperidines has been demonstrated using 'fully green' l-proline nitrate as recyclable room temperature ionic liquid. Recycling of the catalyst was possible up to five runs without loss of catalyst activity.